Building serverless applications with Spring and AWS - Thomas, Marc (Packt, 2018)
"This course will introduce you to Serverless Architecture and lead you to build a simple image-resizing service using a Java-based AWS Lambda function. Then we'll move onto how the Spring framework supports the cloud and in particular AWS. There are a number of different services made available through Spring annotations to make your life easier. Moving on, you'll start to build your Spring-based, serverless application that will take a URL and convert it into a short URL that will be stored in DynamoDB and you'll receive a short URL. You can then use that short URL in a browser and then be redirected to the real site. To demonstrate integration with AWS' Simple Notification Service (SNS), the application will also send a notification to you whenever someone creates a new short URL. Lastly, you'll learn about monitoring your application using AWS cloud watch. By the end of the course, you'll be equipped with the knowledge to build scalable and cost-efficient Spring applications with serverless architectures."--Resource description page